2012
DOI: 10.3390/s120302519
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing and Bacterial Social Interactions in Biofilms

Abstract: Many bacteria are known to regulate their cooperative activities and physiological processes through a mechanism called quorum sensing (QS), in which bacterial cells communicate with each other by releasing, sensing and responding to small diffusible signal molecules. The ability of bacteria to communicate and behave as a group for social interactions like a multi-cellular organism has provided significant benefits to bacteria in host colonization, formation of biofilms, defense against competitors, and adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
356
0
18

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 559 publications
(394 citation statements)
references
References 80 publications
1
356
0
18
Order By: Relevance
“…PJI is a condition with high morbidity and costly economic side effects for endoprosthetic departments [1,2]. The complex pathophysiology of PJI is closely related to the unique microbiological properties of biofilms, generated by microorganisms on artificial materials [3]. Biofilmforming bacteria often remain in a dormant state complicating conventional diagnostic and therapeutic approaches [4].…”
Section: Introductionmentioning
confidence: 99%
“…PJI is a condition with high morbidity and costly economic side effects for endoprosthetic departments [1,2]. The complex pathophysiology of PJI is closely related to the unique microbiological properties of biofilms, generated by microorganisms on artificial materials [3]. Biofilmforming bacteria often remain in a dormant state complicating conventional diagnostic and therapeutic approaches [4].…”
Section: Introductionmentioning
confidence: 99%
“…Both bacteria need tooth surface for colonization. The interaction between S. sanguinis and S. mutans is affected by environmental factors, such as the density of the colony, the availability of nutrition, and pH [8]. Studies by Kreth et al showed that the interaction between S. mutans and S. sanguinis was influenced by conditions in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Clostridium are noted to contain either single or multiple QSS, such as: (1) LuxS, (2) Agr, (3) Agr2 that are regulated by peptide signals e.g., AIP ( Table 1) [24][25][26][27][28][29]. Table 1) [30][31][32][33][34].…”
Section: Clostridiummentioning
confidence: 99%